Avaliação do desenvolvimento da região de Cruzeta (RN), através do uso intensivo de água para irrigação - Araújo, Carlos Alberto Batista de (2007)
This work aims for the evaluation of Cruzeta Irrigated Perimeter, RN, which consists in the efficient use of water for agricultural production. The goal is looking for the available quantity of water for supplying required demands for adequate and economically viable cultures for the region. It is supposed that regional community water is supplied by pipelines from sources located outside of the region. From this study it is recommended the implantation of adequate installments for culture management in accordance with the availability of water resources and others conditionings. It must be considered the intensity of rainy and drought seasons in order to adjust the cultivated area and equipments to be operated, and also, the use of operating models and simulations in order to establish alert levels and eventually, reduction of irrigated area. Based on obtained data it is proposed the cultivation of different types of non-permanent cultures so that temporary cultures would be extensively produced in periods of abundant reservoir storage water permitting the transformation of storage water in storage culture products and few or no production in severe drought periods. This is the basic premise for sustainable agricultural development for Brazilian semiarid region